2018
DOI: 10.1016/j.cdtm.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Customization of therapy for gastroesophageal adenocarcinoma patients

Abstract: Gastroesophageal adenocarcinomas (GEACs) remain a global health problem. These are most often diagnosed at advanced stage and the estimated 5-year relative survival rate is about 5%. Although cure is not possible for patients with advanced GEAC, systemic therapy (chemotherapy or biochemotherapy) can palliate symptoms, improve survival and provide a better quality of life. One of the most promising options for some patients with advanced stage GEAC is immunotherapy, which can result in durable responses. Numero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 89 publications
0
1
0
Order By: Relevance
“…Over the last decade, success of immunotherapy across multiple cancer types has prompted exploration of novel immunologic targets for GECs (85). Recently, the late-line KEYNOTE-059 study of pembrolizumab in PD-L1 positive GEC and gastric tumors showed an objective response rate of 13.3% with 58% of the responses lasting 6 months or longer, leading to a third-line FDA approval (86, 87).…”
Section: Personalized Therapeutic Applicationsmentioning
confidence: 99%
“…Over the last decade, success of immunotherapy across multiple cancer types has prompted exploration of novel immunologic targets for GECs (85). Recently, the late-line KEYNOTE-059 study of pembrolizumab in PD-L1 positive GEC and gastric tumors showed an objective response rate of 13.3% with 58% of the responses lasting 6 months or longer, leading to a third-line FDA approval (86, 87).…”
Section: Personalized Therapeutic Applicationsmentioning
confidence: 99%